Back Cover. Issue 6 (15th February 2023) - Unknown
Abstract : In this review, we first focus our attention on the different properties and synthesis methods of MOFs. Subsequently, we pay attention to the main applications in the field of solar cells. Finally, critical challenges and prospects for MOFs and composite‐based solar cells are proposed. More details are discussed in the article by Chen et al . on page 695—709. Abstract : In this review, we first focus our attention on the different properties and synthesis methods of MOFs. Subsequently, we pay attention to the main applications in the field of solar cells. Finally, critical challenges and prospects for MOFs and composite‐based solar cells are proposed. More details are discussed in the article by Chen et al . on page 695—709.